Pola Asuh Ibu dan Status Gizi Balita - Masita Masita; Marwati Biswan; Erlin Puspita (Politeknik Kesehatan Kemenkes RI Jakarta I, 2018)
Abstract Nutritional state of toddler is one measure of the success of health development, therefore nutrition of toddler need attention. The government has been carrying out activities to improve family nutrition known as the Applied Nutrition Program or the Family Nutrition Program Improvement Effort which provides practical nutrition education to families through the monitoring of infant growth in integrated posyandu, and a whole basic health care package. Factors affecting nutritional status can be distinguished on direct and indirect factors. Direct Factor determined by dietary intake and infectious disease, while the indirect factors include the availability of food in the family, child care, health care and environmental conditions. The purpose: of the study to determine the relationship between parenting mothers with nutritional status of toddler, with dependent variable is nutritional status of children and the independent variables included maternal parenting practices how to feed, how to care for infants, mothers and toddlers hygiene practices as well as external variables include education, employment, economic status and mother's education. Method: uses a cross-sectional study carried out in health center sub-district of Pancoran Mas Depok in June 2011. Samples were mothers with toddlers and collected directly by using the questionnaire. Result: Multivariatble analysis showed a significant relationship between the practice of caring for infants with nutritional status. The mothers who had a bad practice of care for a toddler will have the risk 2 times on incidence of poor nutritional status in infants. In conclusions, the practice of caring for infants and mother knowledge affect the nutritional status of toddler. Statistically there is no significant association between feeding practices, hygiene practices of mothers and infants, maternal education, maternal employment and economic status on the incidence of malnutrition